Buzzwords and fuzzwords: flattening intersectionality in Canadian aid. Issue 2 (4th May 2019) - Mason, Corinne L.
ABSTRACT: In 2017, the Canadian Liberal government introduced the Feminist International Assistance Policy (FIAP), which offers an "intersectional" lens by taking into consideration the diversity of women and girls. This article argues that "intersectional" conceptualized inconsistently in FIAP, and outlines the dissimilar understandings of intersectionality between GAC officials and civil society members. The lack of clarity around intersectionality is predictable given that this issue fuels debates and dialogues in the field of intersectionality theory. As intersectionality has traveled from activist circles to academia and beyond, the theory of intersectionality has often been reduced to a fuzzword and buzzword. Ultimately, this article argues that the impact of this theory on Canadian aid may be quite limited if intersectionality is not clearly and consistently conceptualized.